Analyse Du Rebut Des Cliches Radiographiques Dans Le Service De Radiologie Et Imagerie Médicale Du Chu Campus De Lomé Au Togo - Gbande, P.; Sonhaye, L.; Adambounou, K.; Lambon, K.; N’timon, B.; Dagbe, M.; Agoda-Koussema, L.K.; Adjenou, K.V.; N’dakena, K. (European Scientific Journal, ESJ, 2017)
Purpose: To analyze the waste factors of rejected X-rays films. Methodology: Descriptive and analytical prospective study from 1 January to 30 June 2017 carried out in the department of radiology and medical imaging of the Campus University Hospital of Lomé in Togo. Results: 4912 patients had received 5630 radiographic incidences, including 3288 (58.4%) on the analogy and 2342 (41.5%) on the digital. The reject rate was 12.5%. The vast majority of the X-rays films, 682 (96.9%) were rejected by the radiographers themselves just after development. The resumption frequency ranged from one repeat (550 X-rays films, or 78%) to 4 repeats (8 X-rays films, or 1%). Almost all of the rejected films, 702 (99.7%) came from the analogical room. Chest X-ray was the incidence with more rejection in 33.9% followed by pelvic and lower limb incidences in 21% of cases. More than 2/3 of the rejected films, 473 (67.2%), came from the students' act. The causes of the rejection were mainly centering (25.5%), underexposure (20.17%) and overexposure (12.93). The financial loss caused by the scrap of X-rays films amounted to about 418800F CFA or 638.5 €. Conclusion: Strengthening communication between radiographers and radiologists is necessary to avoid unnecessary repeats of patient’s radiographs.